2020
DOI: 10.46989/001c.21644
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding strategies on growth,body composition, intestine digestive enzymes activities and intestine histology of Megalobrama pellegrini (Tchang, 1930) early juveniles raised in flow-through system

Abstract: To determine the effects of feeding rate and feeding frequency on growth performance, digestive enzymes activities, and intestine development of Megalobrama pellegrini in a replicated flow-through system, we conducted a 42day experiment. We designed three feeding rates (5%, 6.5%, and 8% body weight/day, BW/d) and two feeding frequencies (2 and 3 meals/day; m/d) in this experiment. Fish (0.57 ± 0.01 g) were distributed into 18 tanks with 70 individuals and fed with a commercial diet (33% crude protein, 4% total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Another report (Li et al, 2013) described the effects of starvation and re-feeding on the growth and digestive enzyme activity of juvenile M. pellegrini. At the same time, Qu et al (Qu et al, 2021) conducted a series of analyses on the body weight and optimal feeding frequency of juvenile M. pellegrini in a stream culture mode. The overall growth performance of bream was inferior to that of other sh of the same genus (Li et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…Another report (Li et al, 2013) described the effects of starvation and re-feeding on the growth and digestive enzyme activity of juvenile M. pellegrini. At the same time, Qu et al (Qu et al, 2021) conducted a series of analyses on the body weight and optimal feeding frequency of juvenile M. pellegrini in a stream culture mode. The overall growth performance of bream was inferior to that of other sh of the same genus (Li et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…A recent report indicated that M. pellegrini is omnivorous, with algae and mussels as the primary two food resources (Zhang et al 2020). Moreover, Qu et al (2020) determined that a feeding rate of 6.5% of body weight/d and a feeding frequency of 2 meals/d constituted the optimum feeding strategy for raising this species under laboratory conditions.…”
mentioning
confidence: 99%